Investigations into the structure-function relationship of plant-based surfactant glycyrrhizin: Interfacial behavior & emulsion formation. (February 2020) - Ralla, Theo; Salminen, Hanna; Braun, Katharina; Edelmann, Matthias; Dawid, Corinna; Hofmann, Thomas; Weiss, Jochen
Abstract: This study describes the interfacial and emulsifying properties of a plant-based saponin glycyrrhizin and its aglycone 18 β -glycyrrhetinic acid derived from licorice root ( Glycyrrhiza glabra L.) to enable first insights into a potential structure-function relationship. First, the surface activity of glycyrrhizin and its aglycone at air-water and oil-water interfaces, and the viscoelastic behavior at an oil-water interface was examined. Second, the emulsifying properties by preparing oil-in-water emulsions (100 g oil/kg emulsion, pH 7) by high-pressure homogenization was evaluated. Both glycyrrhizin and its aglycone reduced surface and interfacial activity only <19%, and did not form any viscoelastic interfaces. Nevertheless, glycyrrhizin and its aglycone formed stable oil-in-water emulsions around 0.2 μm at a very low molecule-to-oil ratio. Therefore, the low interfacial activity or interfacial viscoelasticity does not necessarily correlate with the emulsifying capability. Furthermore, molecular modelling of the compounds revealed different hydrophilic-lipophilic balance -values ranging from 1 to 10, and that hydrophobic surfaces dominated over the polar surfaces, indicating that hydrophobic interactions contribute to the stabilizing forces at the interface. The results are relevant for novel 'all-natural' emulsion-based foods, beverages, as well as pharmaceuticals, and cosmetics to enable a potential structure-function relationship for the promising surfactant group of saponins. Graphical abstract: Image 1 Highlights: Licorice root glycyrrhizin and its aglycone showed low surface-activity. Viscoelasticity of formed interface was absent for both molecules. Both molecules formed nano-sized oil-in-water emulsions efficiently. Molecular computing showed differences in hydrophobicity between the molecules.